2023
DOI: 10.1002/aur.2987
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of sibling bullying and mental health in autistic adolescents: The role of self‐esteem

Abstract: Sibling bullying is associated with poor mental health in autistic adolescents. The reasons for this remain unknown. In the current study, we attempted to replicate the existing findings on the direct associations between sibling bullying and mental health in autistic adolescents and expand knowledge by focusing on the indirect associations through self‐esteem. We made use of existing data from the Millennium Cohort Study, a nationally representative UK‐based birth cohort study. We fitted a mediation model to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…These results are consistent with those found in previous studies, so negotiation, as a problem-solving strategy, solves problems in peer relationships [93]. This "cooperative solution of sibling conflict and a general sense of goodwill between siblings certainly can enhance children's adjustment" [58] (p. 10), namely high self-esteem, which can be extended to peer relationships. In addition, siblings can learn from siblings to solve problems or negotiate, and this can contribute as a protective factor in other contexts [94].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are consistent with those found in previous studies, so negotiation, as a problem-solving strategy, solves problems in peer relationships [93]. This "cooperative solution of sibling conflict and a general sense of goodwill between siblings certainly can enhance children's adjustment" [58] (p. 10), namely high self-esteem, which can be extended to peer relationships. In addition, siblings can learn from siblings to solve problems or negotiate, and this can contribute as a protective factor in other contexts [94].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, victimization due to psychological and physical aggression with severe damage seems to predict lower levels of self-esteem, which, in turn, predicts greater school victimization through social exclusion and verbal aggression. Thus, it is suggested that being a victim of aggressive behavior on the part of siblings predisposes the adolescent to low self-esteem [14,58]. As a result, the adolescent, considering themselves to be undeserving of love and affection, also becomes vulnerable to aggression by the peer group, being vulnerable to bullying [62,67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the self-rating instruments, evidence of reliability (i.e., internal consistency) in the adequate to excellent range was reported for the ASEBA-Youth Self-Report (YSR) (Mazefsky et al, 2014), SDQ (Deniz & Toseeb, 2023;Khor et al, 2014), and RCADS (Khalfe et al, 2023;Sterling et al, 2015). Evidence of good or excellent internal consistency and convergent validity was observed for the Depression, Anxiety and Stress Scale (DASS-21; Lovibond & Lovibond, 1995;Park et al, 2020) and Hospital Anxiety and Depression Scale (HADS; Uljarevic et al, 2018;Zigmond & Snaith, 1983).…”
Section: Psychometric Quality Of Instruments For Assessing Mhmentioning
confidence: 98%
“…Regarding the study population, there was a notable lack of population-based studies (only 7% of the investigations: ABC: Chua et al, 2023;Rohacek et al, 2023 Deniz & Toseeb, 2023;Milosavljevic et al, 2016;Totsika et al, 2013), with the majority being convenience samples with participants recruited from clinics and other preexisting services. A significant proportion of the papers (26%; n = 43) relied on parent-reported clinical autism diagnoses or diagnoses derived from enrollment in schools for autistic people (see Appendix F for the risk of bias assessment).…”
Section: Mh Assessment Instrumentsmentioning
confidence: 99%